Silica coating influences the corona and biokinetics of cerium oxide nanoparticles. Issue 1 (December 2015) - Konduru, Nagarjun; Jimenez, Renato; Swami, Archana; Friend, Sherri; Castranova, Vincent; Demokritou, Philip; Brain, Joseph; Molina, Ramon
Abstract Background The physicochemical properties of nanoparticles (NPs) influence their biological outcomes. Methods We assessed the effects of an amorphous silica coating on the pharmacokinetics and pulmonary effects of CeO2 NPs following intratracheal (IT) instillation, gavage and intravenous injection in rats. Uncoated and silica-coated CeO2 NPs were generated by flame spray pyrolysis and later neutron-activated. These radioactive NPs were IT-instilled, gavaged, or intravenously (IV) injected in rats. Animals were analyzed over 28 days post-IT, 7 days post-gavage and 2 days post-injection. Results Our data indicate that silica coating caused more but transient lung inflammation compared to uncoated CeO2 . The transient inflammation of silica-coated CeO2 was accompanied by its enhanced clearance. Then, from 7 to 28 days, clearance was similar although significantly more141 Ce from silica-coated (35 %) was cleared than from uncoated (19 %)141 CeO2 in 28 days. The protein coronas of the two NPs were significantly different when they were incubated with alveolar lining fluid. Despite more rapid clearance from the lungs, the extrapulmonary141 Ce from silica-coated141 CeO2 was still minimal (<1 %) although lower than from uncoated141 CeO2 NPs. Post-gavage, nearly 100 % of both NPs were excreted in the feces consistent with very low gut absorption. Both IV-injected141 CeO2 NP types were primarily retained in the liver and spleen. The silica coating significantly altered the plasma protein corona composition and enhanced retention of141 Ce in other organs except the liver. Conclusion We conclude that silica coating of nanoceria alters the biodistribution of cerium likely due to modifications in protein corona formation after IT and IV administration.